Function of Chick Subcutaneous Adipose Tissue During the Embryonic and Posthatch Period - Zhao, Haidong; Wu, Mingli; Tang, Xiaoqin; Li, Qi; Yi, Xiaohua; Wang, Shuhui; Jia, Cunling; Wei, Zehui; Sun, Xiuzhu (Frontiers in Physiology, 2021)
Since the excess abdominal fat was one of the main problems in broiler industry for the development of modern broiler and layer industry, the importance of subcutaneous adipose tissue has been neglected. However, chicks subcutaneous adipose tissue appeared earlier than abdominal adipose tissue, and more than abdominal adipose tissue. Despite a wealth of data, detailed information is lacking about the development and function of chicks subcutaneous adipose tissue during the embryonic and posthatch period. Therefore, the objective of the current study was to determine developmental changes of adipocyte differentiation, lipid synthesis, lipolysis, fatty acid β-oxidation and lipid contents from E12 to D9.5. The results showed that subcutaneous adipose tissue was another important energy supply tissue during the posthatch period. In this stage, the mitochondrial copy number and fatty acid β-oxidation level significantly increased. It revealed that chick subcutaneous adipose tissue not only has the function of energy supply by lipidolysis, but also performs the same function as brown adipose tissue to some extent, in spite of the brown adipose tissue does not exist in birds. In addition, this finding improved the theory of energy supply in the embryonic and posthatch period, and might provide theoretical basis on physiological characteristics of lipid metabolism in chicks.